Factors influencing reselection of village doctors in rural-oriented tuition-waived medical education program in Shanghai, China: a cross-sectional study - Jing Gao; Juhua Zhang; Chenlei Shi; Aiqin Fan; Peng Zhang (Frontiers in Public Health)
BackgroundIn order to actively cultivate a new generation of village doctors (NGVDs) who possess a high level of education, provide high-quality healthcare services, Shanghai Municipal Health Bureau, together with the Municipal Education Commission, Municipal Finance Bureau, and Municipal Agriculture Commission initiated Rural-oriented Tuition-waived Medical Education (RTME) in 2006. This study aims to identify the factors that influence the reselection intention and perceptions of NGVDs of RTME program in Shanghai.MethodsIn 2023, a questionnaire survey was conducted among a sample of NGVDs enrolled in the RTME program in 8 districts of Shanghai. The research focused on five aspects, including demographic characteristics, job characteristics, reasons for choosing RTME, career identity and job satisfaction. The participants were asked questions related to their experiences, opinions, and perceptions. Analysis of variance (ANOVA), chi-square tests and logistic regression analysis was conducted.ResultsA total of 419 questionnaires were collected. The majority (64.44%) indicated they would reselect this career, while 35.56% expressed either no preference or indifference. Factors influencing reselection included “Volunteering to serve the grassroots people” (odds ratio [OR], 2.29 [95% confidence interval CI, 1.22–4.30]), “Enjoying the medical profession” (OR, 2.64 [95%CI, 1.33–5.27]), not fulfilling family wishes (OR, 0.47 [95%CI, 0.24–0.88]), Satisfied with the current salary (OR, 2.39 [95%CI, 1.27–4.49]). NGVDs who think village doctors can leverage their professional ability with “okay” (OR, 32.87 [95%CI, 3.69–293.64]) and “yes” (OR, 120.03 [95%CI, 12.78- > 999.99]) and who think NGVDs were “important” (OR, 3.74 [95%CI, 1.21–11.55]) were more inclinatively to reselect to be NGVD.ConclusionReasons for choosing RTME, understanding of the government’s policy, career identity, and job satisfaction were all influence the reselection of RTME. This research can contribute to the improvement and development of similar programs in the future, benefiting both the students and the healthcare system as a whole.